Synthesis and Biological Evaluation of New 5-Fluorouracil-Substituted Ampelopsin Derivatives - Zhou, Wei-Ming (Molecules, 2010)
This study reports two novel 5-fluorouracil-substituted ampelopsin derivatives. The structures of two new derivatives were characterized by elemental analysis, (1)H-NMR, (13)C-NMR, IR and MS. Their anticancer activities in vitro against two cancer cell lines, K562 and K562/ADR, were investigated using the MTT assay, and the results showed that the two new compounds were more effective than reference drugs such as ampelopsin and verapamil.